On Cognitive Approach to Language when Studying Russian Prefixes Expressing Relation to the Norm; Procedia - Social and Behavioral Sciences; Vol. 215 : International Education and Cross-Cultural Communication, Problems and Solutions, (IECC 2015) - Efanova L. G. Larisa Georgievna; Lutoshkina O. S. Olga Sergeevna; Dronova L. P. Lubov; Natsagdorj Sugarmaa (2015, 2015)
Title screen